Environmental aspects in accounting - Nagy, Gábor (Acta Agraria Debreceniensis, 2013)
By the strengthening of the economic competition became it apparent a company can’t be valued separate, it should be examined as a complex system. In the assessment of corporate performance is increasingly emphasized the environmental performance. The relevant information of stakeholder about the environmental performance is todays an expection, For this, a management control system is needed, which provide relevant information to managers, hence facilitating the informed decision. This study highlighted, accounting systems are able to meet this demand sufficiently, the accounting means not only the usual bookkeeping, it can be interpreted as a management-controll system, which can help in the valuation of the environmental performance.